(untitled) (Research, Society and Development, 2022)
Objective: The study seeks to understand how the production of podcasts in medical education contributes to significant academic learning. Methodology: It has a qualitative character of the experience report type with a focus on podcast production since 2018 by students of the Higher Education Institution (HEI) in parallel with a discipline of the mandatory curriculum of the medical course. Results and Discussion: The strategies of active methodologies contribute to the teaching-learning process, as it encourages the student to be the protagonist of the construction of their knowledge. The current study demonstrates the applicability and effectiveness of technological tools that allow effective teaching - such as podcasts - in times of adversity such as the current COVID-19. Conclusion: Podcasts developed by academics generate a role reversal where the student makes become the protagonist of their learning, fostering a contextualized and timely process for the realization of undergraduate teaching. Given the lack of studies in the literature that report the use of podcasts in the medical course, it is intended that this proposal can serve as a reference for new practices.